Codifying Deliberative Democracy within the EU in the Digital Era - MarÍa Jesus GarcÍa GarcÍa (Bulgarian Journal of International Economics and Politics, 2025)
The main objective of this paper is to analyse the necessity of institutionalizing deliberative democracy processes in the framework of EU democracies. The rationale behind this paper comes from the fact that governments have been experimenting with innovative practices in the field of deliberative democracy to in order to make the public participate in decision-making. However, these experimental practices do not create citizens’ entitlements, nor public power duties. The purpose of this paper is to raise awareness of the importance of coming up with a set of legal standards, based on the EU acquis, in order to guarantee democratic cohesion when codifying the functioning and operation of deliberative democracy, anticipating the potential impact of AI-supported deliberative methods. The hypothesis is that codification and institutionalization of deliberative democracy is necessary to preserve democratic cohesion among EU member states and also to guarantee citizens’ entitlements. As for methodology, data collection and data analysis constitute the bulk of the research. Data collection relies on literature, and EU legislation. Data analysis is based on legal reasoning, mainly. The conclusion is that citizens’ participation needs to be secured and guaranteed by means of a set of core principles based on the EU acquis in order to preserve democratic cohesion among member states. Otherwise, no rights are conferred to citizens and deliberative processes operate at the discretion of public authorities.